PENGOLAHAN BAHAN ORGANIK ECENG GONDOK MENJADI MEDIA TUMBUH UNTUK MENDUKUNG PERTANIAN ORGANIK - Sittadewi, Euthalia Hanggari (Jurnal Teknologi Lingkungan, 2007)
Eceng gondok (Eichornia crassipes (Mart)(Solms) is a floating plants that creates problems on the maximum of waters utilization. On the other side, eceng gondok is a potential organic matter that can be used for a growing media. The utilization of the organic matter for growing media will support of organic farming and minimize the use of chemical materials. Process of eceng gondok decomposition can produce a growing media with high nutrients contain for plants growth. The experiments of growing media from eceng gondok for sawi hibrid plants show positive respons in which the plant has freshly growth and free of diseases.